On the two guiding ideas of pragmatic anthropology in the critical thought of Immanuel Kant - Arias Albisu, Martín (2022)
According to Kant, there are two ideas of practical reason within the framework of his Anthropology from a pragmatic point of view. The first idea is that of the human being as a free agent situated in a world. The second idea is that of a cosmopolitan society.